Kajian Pustaka Mengenai Restaurant Atmosphere - Adeline Agoes; Nami Fitricia Pasaribu (Binus Business Review, 2015)
Restaurant is one of the businesses that support tourism development. Restaurants nowadays don’t only provide food, but also the service and atmosphere to their customers. The purpose of this study is to discover theaspects defining restaurant atmosphere and the implications of restaurant atmosphere to other particular aspects related to restaurant business. This article is written based on a study conducted through a literature review. Through the examination, it is found that the atmosphere of a restaurant is one important aspect and can be considered as a competitive advantage as well as one of the determinants of customer satisfaction.